TINJAUAN YURIDIS TERHADAP KEABSAHAN DAN KEKUATAN ALAT BUKTI JUAL BELI TANAH MENURUT HUKUM ADAT - Tiar Ramon (Fakultas Hukum Universitas Islam Indragiri, 2018)
Land buying and selling according to customary law needs to know the validity and strength of the evidence, so that if a claim can be maintained in court. The formulation of the problem of this research is how a juridical review of the validity and strength of evidence of land buying and selling according to customary law. The research method used is normative legal research. The results of the discussion indicate that a juridical review of the validity of buying and selling according to customary law is legal as in the Supreme Court Jurisprudence Number 952k / Sip / 1974 that buying and selling is legal in fulfilling the requirements of customary law, in real, cash and known by the Head of Village / Head The village, while the strength of the evidence is that if the land is bought verbally, the strength of the evidence is free, whereas if done in writing, the strength of the evidence is the beginning and will be perfect if acknowledged by the parties or supported by other evidence tools such as evidence statement from 2 witnesses